Clinical approaches to minimize iatrogenic weight gain in children and adolescents. Issue 1 (28th September 2020) - Sweeney, Brooke; Kelly, Aaron S.; San Giovanni, Christine B.; Kelsey, Megan M.; Skelton, Joseph A.
Summary: Clinical providers may underestimate the role of management of diseases that can occur with obesity, termed co‐morbid conditions, distinct from disease that arise as a result of obesity, co‐morbidities. Many of these conditions are associated with iatrogenic weight gain, and can interfere with weight loss outcomes in children and adolescents with obesity. Management of co‐morbid conditions, and thoughtful selection of medications associated with weight neutrality or weight loss may increase the effectiveness of obesity treatment strategies. The aim of this commentary is to summarize the literature and discuss considerations for obesity treatment in the context of the more complicated patient, which often requires strategic management of co‐morbid conditions and minimizing iatrogenic weight gain.